Eigen Face Vector (EFV) based Personal Assistant through Facial Image Recognition - Jayasingh, J Roopa; Kumar, R J S Jeba; Sagayam, K Martin; Ali, Hanafy M (Turkish journal of computer and mathematics education, 2021)
This research paper is carried out  to  solve the issue faced in the busy life of the entire human race to complete all the necessary daily work within a restricted time limit. These compromises in job completion  leads to both  problems in society and self degradation. This paper talks about the novel low cost personal reminder hub for commons using eigen face vector recognition and reduced Personal Component Analysis (PCA).Personal face recognition, voice reminder which is trained is provided with appropriate reminders to inform us during our busy problems. We  train the reminders inorder to find out each person’s face average weight parameters which is calculated using cluster matrix calculation.When the recipient of the reminder fixes his face in the face recognistion field, hub acquires the face image and tries to  compare wth the captured threshold value to all the prelearnt separate threshold values.From the right match with consideration of minimal deviation the face is lightly recognised and the required saved reminder is informed through the inbuilt voice which would change according to our taste. Thus the efficient method of face identification voice reminder for reduced low cost personal reminder is built and this will be helpful for all busy working people and  for family reminders like childrens or working people task reminder, patient tablet reminder etc.